The appearance of scalp high‐frequency oscillations is associated with poor seizure control in pediatric epilepsy patients - Keisuke Maeda; Nami Hosoda; Himari Tsuboi; Honoka Naito; Chiaki Kudo; Junichi Fukumoto; Shiho Fujita; Naohiro Ichino; Keisuke Osakabe; Keiko Sugimoto; Shunta Yamaguchi; Naoko Ishihara (Epilepsia Open)
Abstract Objective Epilepsy treatment with anti‐seizure medications (ASMs) is based on careful assessment of the balance between the likelihood of further seizures and the risk of side effects of treatment. However, there is currently no established biomarker to ascertain seizure control status with ASMs. High‐frequency oscillations (HFOs), transient bursts of EEG activity with frequencies beyond 80 Hz, are a new and promising noninvasive epilepsy biomarker. We compared the risk of scalp HFO appearance between pediatric patients with good and poor seizure control by treatment with ASMs. Methods A total of 72 epilepsy patients (aged 0–18 years, 39 males) with good and poor seizure control with ASMs participated in this study. We applied a validated automated detector to determine HFO and spike. We calculated the odds ratios (ORs) for scalp HFO and spike appearance according to seizure control status by multiple logistic regression analysis. Results Scalp HFO was seen more commonly and with a significantly higher detection rate in patients with poor seizure control as compared with patients with good seizure control for both ripple and fast ripple. These significant associations were found for both focal and generalized epilepsy. The ORs for scalp HFO appearance adjusted for confounding factors were significantly higher in patients with poor seizure control compared to those with good seizure control (ripple: OR [95% CI] = 11.91 [2.21–64.30], p = 0.004; fast ripple: 4.98 [1.03–24.09], p = 0.046). There were no significant associations between spike appearance and seizure control status. Significance We found an increased risk of scalp HFO appearance in patients with poor seizure control. The results of this study support that scalp HFO is associated with patients having frequent seizures after treatment in both ripple and fast ripple. Plain Language Summary This study analyzed scalp high‐frequency oscillations and spikes in pediatric patients with various types of epilepsy who were being treated using ASMs. The results showed that an increased risk of scalp HFO appearance was observed in patients with poor seizure control compared to those with good seizure control. These findings were observed in both the ripple (80–250 Hz) and fast ripple (250–500 Hz) bands. The scalp HFO is associated with patients having frequent seizures after treatment in both ripple and fast ripple.